FATAL LATERAL THORACIC ARTERY INJURY BY A NON BALLISTIC METAL PIECE EJECTED FROM A ROLLING MACHINE-A CASE REPORT (Journal of Forensic Medicine & Toxicology, 2014)
Fatal penetrating injuries caused by missile released from firearms and during bomb blasts are well known.Accidental non ballistic penetrating injury to lateral thoracic artery is very rare. In the instant case, a worker, who was working on a rolling stainless steel machine, sustained a penetrating chest injuryby a metallic object ejected at high speed from rolling machine. Sharp edged metallic piece entered into right axilla and successfully made a rent in right lateral thoracic artery. He was taken to hospital but died during course of treatment. At autopsy a stainless steel metallic piece was recovered from chest cavity. It is the first case; in which lateral thoracic artery is injured in accidental manner by sharp metallic piece. Through this article we have discussed post mortem findings and emphasized on the importance of wearing protective clothes while working in industrial setup.
Keywords: Non ballistic injury; Lateral thoracic artery; Rolling machine